Respuesta :

Answer:

Step 2:

For Completing the square,

[tex](\frac{1}{2} coefficient\ x)^{2} =(\frac{1}{2}\times \frac{1}{2})^{2}=\frac{1}{16}[/tex]

Add half coefficient of x square on both the side we get

[tex]x^{2}+\dfrac{x}{2}+\frac{1}{16}=2+\frac{1}{16}[/tex]

Step-by-step explanation:

Solve:

[tex]2x^{2}+x-4=0[/tex]

[tex]2x^{2}+x=4[/tex]

Solution:

Step 1:

Dividing both the side by two we get

[tex]x^{2}+\dfrac{x}{2}=2[/tex]

Step 2:

For Completing the square,

[tex](\frac{1}{2} coefficient\ x)^{2} =(\frac{1}{2}\times \frac{1}{2})^{2}=\frac{1}{16}[/tex]

Add half coefficient of x square on both the side we get

[tex]x^{2}+\dfrac{x}{2}+\frac{1}{16}=2+\frac{1}{16}[/tex]

Step 3:

We know [tex](a +b)^{2} = a^{2}+2ab +b^{2}[/tex]

[tex](x+\frac{1}{4})^{2}=\frac{33}{16} \\ \\(x+\dfrac{1}{4})=\pm \sqrt{\dfrac{33}{16}} \\\\x=-\dfrac{1}{4}\pm \sqrt{\dfrac{33}{16}}[/tex]

ACCESS MORE